ИДЕИ МОСКОВСКОЙ ШКОЛЫ ФУНКЦИОНАЛЬНО-КОММУНИКАТИВНОЙ ГРАММАТИКИ В ТРУДАХ ПОЛЬСКИХ РУСИСТОВ - Fontański, Henryk (Przegląd Rusycystyczny, 2016)
IDEE MOSKIEWSKIEJ SZKOŁY GRAMATYKI FUNKCJONALNO-KOMUNIKACYJNEJ W PRACACH POLSKICH RUSYCYSTÓW W artykule omówiono publikacje polskich rusycystów, którzy w swoich badaniach wykorzystują idee teoretyczne Galiny Zołotowej, twórczyni moskiewskiej szkoły gramatyki funkcjonalno-komunikacyjnej. W przeglądzie uwzględnione zostały prace, w których istotną rolę odgrywają takie postulaty gramatyki funkcjonalno-komunikacyjnej, jak dwuczłonowość zdania elementarnego, model zdaniowy i jego modyfikacje, typologia syntaktemów, klasyfikacja semantyczno-składniowa czasowników, typy predykatów oraz tzw. rejestry komunikacyjne. IDEAS OF THE MOSCOW SCHOOL OF FUNCTIONAL AND COMMUNICATIVE GRAMMAR IN WORKS OF THE POLISH SPECIALISTS IN RUSSIAN LINGUISTICS The present article offers a review of works by Polish specialists in Russian linguistics, who use in their research theories and ideas developed by Galina Zolotova, a founder of the Moscow school of functional and communicative grammar. The attention is concentrated on such notions as a principle of a binomial sentence, concept of a model of the sentence and its modifications, typology of syntactic forms of words in Russian, semantico-syntactical classification of verbs and types of predicates, and also so-called communicative registers.